The Huaqiao Warriors : Chinese Resistance Movement in the Philippines, 1942-45 - Yung Li, Yuk-wai (Book collections on Project MUSE., 1995)
Among the extremely limited English language literature on the Chinese resistance movement in the Philippines during the Japanese occupation, this book is unique in making use of documents from the United States National Archives, supplemented by memorials and articles recently published in China and the Philippines. While the reliability of these original sources is questionable, the difficulty of interpreting these sources was dealt with openly and effort was made to compare contradictory accounts objectively. Meanwhile, the characteristics of the Chinese resistance movement were summarized in its historical social context, and the long-term effect of the resistance movement on the Chinese community in the Philippines was addressed. The book thus fills an important gap in Philippine historiography on the Second World War and in the understanding of the Philippine Chinese community and the effect of Japanese occupation upon it.